Long-term effects of psychotherapy in a context of continuous community and gang violence: changes in aggressive attitude in high-risk South African adolescents. Issue 1 (31st January 2020) - Hinsberger, Martina; Holtzhausen, Leon; Sommer, Jessica; Kaminer, Debra; Elbert, Thomas; Seedat, Soraya; Augsburger, Mareike; Schauer, Maggie; Weierstall, Roland
Abstract: Background: Post-traumatic stress but also aggressive attitudes and behaviour can be found in adolescents living in a context of ongoing community and gang violence in the low-income urban areas of Cape Town, South Africa. Aims: We investigated the long-term effects (15–20 months after therapy) of (a) Narrative Exposure Therapy for Forensic Offender Rehabilitation (FORNET) and (b) the cognitive behavioural intervention 'Thinking for a Change' (CBT) on post-traumatic stress disorder (PTSD) and aggression compared with a waiting list. Method: Fifty-four young males participated in the treatment trial, of which 17 completed the FORNET intervention, 11 the CBT intervention, and 26 were on a waiting list. The primary outcome was the change score for the Appetitive Aggression Scale; secondary outcomes were the PTSD Symptom Scale-Interview change scores, and the number of perpetrated violent event types. Results: The reduction in scores for PTSD that had been observed in FORNET completers at the first follow-up were still significant at the second long-term follow-up (Cohen's d = 0.86). In this treatment arm (FORNET), the scores for appetitive aggression were also significantly reduced (Cohen's d = 1.00). There were no significant changes observed for CBT or for the waiting list. Conclusions: The study indicates that FORNET can successfully reduce post-traumatic stress as well as the attraction to violence even for individuals living under conditions of continuous traumatic stress.